Hydrogen Generation During Thermal Processes of Water Decomposition on the Surface of Nano-ZrO2+3mol.%Y2O3 - Imanova, Gunel; Asgerov, Elmar; Jabarov, Sakin; Mansimov, Zaur; Kaya, Mustafa; Doroshkevich, Aleksandr (Trends in Sciences, 2023)
The study of physicochemical properties of nano-ZrO2+3mol.%Y2O3 was determined. The X-ray diffraction spectrum of the nano-ZrO2 and system nano-ZrO2+3 mol.%Y2O3 compound was drawn by the Ritveld method and the crystal structure was determined at different temperatures (T = 373, 473, 573, 673 K) and under normal conditions. The energy of the arrangement of H2 as a result of the decay of H2O, on the surface of nano-ZrO2+3mol.%Y2O3 was considered. Impacts of adsorption and desorption preparation of ZrO2+3mol.%Y2O3 nanoparticles were considered at diverse (T = 373, 473, 573, 673 K) temperatures. The thought of H2 in warm forms at nano-ZrO2+3mol.%Y2O3 framework expanded. This tells about hydrogen era by water part in close future. Nano-ZrO2 and system nano-ZrO2+3mol.%Y2O3 with the temperature range of T = 373, 473, 573, 673 K have been studied by SEM analysis. These results are promising of hydrogen generation by water splitting in near future. HIGHLIGHTS First innovative research article in this area Importance of the thermal in water splitting for hydrogen generation Design and optimization of water splitting for hydrogen generation Future of hydrogen generation at a large scale economically GRAPHICAL ABSTRACT